FACTORS ASSOCIATED WITH DISABILITY IN SYMPTOMATIC KNEE OSTEOARTHRITIS - Funda Levendoğlu,; Ali Sallı,; Hatice Uğurlu, (Archives of Rheumatology, 2004)
Objectives: The aim of this study was to assess the impact of clinical and psychosocial variables on disability in knee osteoarthritis (OA). Methods: The subjects (n=82) were outpatients. Self-reported disability was measured by the Western Ontario and McMaster universities (WOMAC 3.0) OA index. Pain was measured by the Visual analog scale and the WOMAC pain questionnaire. Depression was assessed with Beck Depression Inventory. Quality of life were measured by Nottingham Health Profile 1. A detailed knee examination was performed. Results: The mean age was 56.3 ± 8.0 year with a mean symptom duration of 5.6 ± 5.0 yr. There were significant relationship between physical function score of WOMAC and pain, depression and quality of life scores (p<0.05). The mean WOMAC disability score for obese subjects (BMI>30) was significantly higher than the non-obese(p<0.05). Pain on motion, joint line tenderness and tenderness on patellofemoral compression, crepitus and instability of ligaments were also associated with increased WOMAC disability scores (p<0.05). Conclusions: Disability is related to pain severity, BMI, depression and quality of life. Health interventions in OA, primary focused on pain and weight reduction, could be supplemented with psychologic support to enhance health outcomes.